In Vitro Antibacterial Interaction of Doripenem and Amikacin against Multidrug-Resistant Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae Isolates - Tonny Loho; Ninik Sukartini; Dalima A. W. Astrawinata; Suzanna Immanuel; Diana Aulia; Ika Priatni (Canadian Journal of Infectious Diseases and Medical Microbiology)
Evaluation of the in vitro interaction of doripenem and amikacin against Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae was done by classifying them into four groups: doripenem and amikacin sensitive (DOR-S/AMK-S), doripenem sensitive and amikacin resistant (DOR-S/AMK-R), doripenem resistant and amikacin sensitive (DOR-R/AMK-S), and both doripenem and amikacin resistant (DOR-R/AMK-R). The MIC of each antibiotic and their combination was obtained using the Etest method. The fractional inhibitory concentration index was calculated to classify the results as synergistic, additive, indifferent, or antagonistic interaction. In the DOR-S/AMK-S class, 1 isolate of A. baumannii showed synergy and the other 5 showed additive results, 5 isolates of P. aeruginosa showed additive and 1 isolate showed indifferent result, and 2 isolates of K. pneumoniae showed additive and the other 4 showed indifferent results. In the DOR-S/AMK-R class, 3 isolates of A. baumannii showed additive and the other 3 showed indifferent results, 2 isolates of P. aeruginosa showed indifferent results, and 1 isolate of K. pneumoniae showed additive and the other 5 showed indifferent results. In the DOR-R/AMK-S class, 1 isolate of A. baumannii showed additive and the other 5 showed indifferent results, 1 isolate of P. aeruginosa showed additive and the other 5 showed indifferent results, and 4 isolates of K. pneumoniae showed additive and the other 2 showed indifferent results. In the DOR-R/AMK-R class, 6 isolates of A. baumannii showed indifferent results, 1 isolate of P. aeruginosa showed additive and the other 5 showed indifferent results, and 1 isolate of K. pneumoniae showed additive and the other 5 showed indifferent results. Synergy occurred in only 1 (1.5%) isolate. Additive interaction occurred in 24 (35.3%) isolates, and indifferent interaction occurred in 43 (63.2%) isolates. Doripenem sensitive combined with amikacin sensitive reduced MIC significantly in all bacterial isolates when compared to single MIC of each antibiotic.